2009
DOI: 10.1258/ijsa.2008.008434
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health of adults working in pornographic films

Abstract: We report the frequency of sexually transmitted infections (STIs) diagnosed in performers in the adult pornographic film industry. Over a 13 month period, 445 STI screens were performed in 115 patients, 56 women and 59 men. All reported unprotected sex during filming. Seventy-five percent (86) had at least one sexual partner outside work, and 90% used condoms inconsistently with them. Women worked exclusively with women (23%), men only (38%) or both genders (39%). Almost all men (97%) worked exclusively hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 2 publications
0
3
0
16
Order By: Relevance
“…This may support recommendations for three-site anatomical testing for gonorrhoea and chlamydia to reduce a possible reservoir of missed infections. 4 To conclude, a challenging interplay exists between performers, healthcare providers and film producers in attaining and improving sexual health among these sex workers. To address any deficits in optimum service provision, there is a need to develop specific UK national guidance for clinicians, including improved collaboration with established AFI organisations such as United Kingdom Adult Producers (UKAP) and 'PORN4PREP'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may support recommendations for three-site anatomical testing for gonorrhoea and chlamydia to reduce a possible reservoir of missed infections. 4 To conclude, a challenging interplay exists between performers, healthcare providers and film producers in attaining and improving sexual health among these sex workers. To address any deficits in optimum service provision, there is a need to develop specific UK national guidance for clinicians, including improved collaboration with established AFI organisations such as United Kingdom Adult Producers (UKAP) and 'PORN4PREP'.…”
Section: Discussionmentioning
confidence: 99%
“…human immunodeficiency virus (HIV), syphilis, gonorrhoea and chlamydia. Research in USA and UK on AFPs report that sexual intercourse is condomless 80%-90% of the time, [2][3][4][5][6][7] and the prevalence of STI is between 8% and 35%.…”
Section: Introductionmentioning
confidence: 99%
“…Dans les trois autres études, les acteur.trices étaient majoritairement britanniques (72 % à 100 %; Coyne et al, 2009;Hill et al, 2009;King et Evans, 2020). Une étude démontre que comparativement à un groupe de non-actrices pornographiques de Californie, une plus grande proportion d'actrices pornographiques a déclaré être noire, mais une plus petite proportion a déclaré être hispanique, blanche ou asiatique (Grudzen et al, 2013).…”
Section: Caractéristiques Démographiquesunclassified
“…De plus, comparativement aux groupes composés de nonacteur.trices, les acteur.trices pornographiques étaient significativement plus préoccupé.es par le risque de contracter une ITSS et étaient plus permissif.ves quant au nombre de partenaires sexuel.les antérieur.es de leur partenaire actuel . Au total, neuf études ont documenté l'utilisation du préservatif lors des relations sexuelles (Coyne et al, 2009;Grudzen et al, 2009Grudzen et al, , 2011Grudzen et al, , 2013Hill et al, 2009;Javanbakht et al, 2017;King et Evans, 2020;Rodriguez-Hart et al, 2012). Les résultats démontrent que la majorité des acteur.trices pornographiques n'utilisent pas de préservatif dans leur vie professionnelle ou l'utilisent rarement (Coyne et al, 2009;Grudzen et al, 2009Grudzen et al, , 2011Grudzen et al, , 2013Hill et al, 2009;Javanbakht et al, 2017;King et Evans, 2020;Rodriguez-Hart et al, 2012).…”
Section: Comportements Sexuelsunclassified
“…Sir: In their recent report, Coyne et al 1 reported low rates of consistent condom use and high prevalence of sexually transmitted infections (STI) among patients attending their clinic who work in the adult entertainment industry (AEI). This mirrors our own experience, with some notable differences.…”
mentioning
confidence: 99%